A Novel Clinical-Radiomics Model Pre-operatively Predicted the Stone-Free Rate of Flexible Ureteroscopy Strategy in Kidney Stone Patients - Xun, Yang; Chen, Mingzhen; Liang, Ping; Tripathi, Pratik; Deng, Huchuan; Zhou, Ziling; Xie, Qingguo; Li, Cong; Wang, Shaogang; Li, Zhen; Hu, Daoyu; Kamel, Ihab (Frontiers in Medicine, 2020)
Purpose To develop and validate a novel clinical-radiomics nomogram model for preoperatively predicting stone-free rate of flexible ureteroscopy (fURS) in kidney stone patients. Patients and Methods Altogether 2129 fURS cases with kidney stone were retrospectively analyzed, and 264 patients with solitary kidney stone were included in further study. For lower calyx calculi, a radiomics model was generated in a primary cohort of 99 patients who underwent non-contrast enhanced computed tomography (NCCT). Radiomics feature selection and signature building were conducted by using the least absolute shrinkage and selection operator (LASSO) method. Multivariate logistic regression analysis was employed to build a model incorporating radiomics and potential clinical factors. Model performance was evaluated by its discrimination, calibration, and clinical utility. The model was internally validated in 43 patients. Results The overall success rate of fURS was 72%, while the stone-free rate (SFR) for lower calyx calculi and non-lower calyx calculi was 56.3% and 90.16%, respectively. On multivariate logistic regression analysis of the primary cohort, independent predictors for SFR were radiomics signature, stone volume, operator experience, hydronephrosis level, which were all selected into the nomogram. The AUC of clinical-radiomics model was 0.949 and 0.947 in primary and validation cohort, respectively. Moreover, the calibration curve showed satisfactory predictive accuracy, and the decision curve analysis indicated that the nomogram has superior clinical application value. Conclusion In this novel clinical-radiomics model, the radiomics scores, stone volume, hydronephrosis level and operator experience were crucial for the flexible ureteroscopy strategy.